Предмет: Алгебра, автор: irochka5

3tg(п/7)-9tg(13п/7)/-2ctg(33п/14)

Ответы

Автор ответа: NNNLLL54
0
frac{3tgfrac{pi}{7}-9tgfrac{13pi}{7}}{-2ctgfrac{33pi}{14}}=frac{3tgfrac{pi}{7}-9tg(2pi -frac{pi}{7})}{-2ctg(2pi +frac{5pi}{14})}=frac{3tgfrac{pi}{7}+9tgfrac{pi}{7}}{-2ctgfrac{5pi}{14}}=-6frac{tgfrac{pi}{7}}{ctg{frac{5pi}{14}}}=\=-6frac{{{sinfrac{pi}{7};sinfrac{5pi}{14}}}}{cosfrac{5pi}{14}cosfrac{pi}{7}}=-6frac{cosfrac{3pi}{14}-cosfrac{pi}{2}}{cosfrac{pi}{2}+cosfrac{3pi}{14}}=-6frac{cosfrac{3pi}{14}}{cosfrac{3pi}{14}}=-6
Похожие вопросы
Предмет: Алгебра, автор: eponomar99